Transformational Leadership On Work Mativation : Systematic Literatur Review Overview SLR - Nadia Duerasor; Sopiah Sopiah (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
The purpose of this LSR is to determine the influence of transformational leadership variables on work motivation or performance determinants in companies. This research examined and reviewed 38 journal articles from two databases, Science Direct, Emerald Insight, and Scopus, from Publish or Parish, from 2019 to 2023. The analysis used PRISMA screening to obtain 38 articles. In this research we examine the benefits of transformational leadership in supporting employees to achieve goals that influence their behavior. In other words, we examine how organizations can use transformational leadership to develop employees. The aim of this research is to determine the influence of transformational leadership variables on work motivation variables. It has been found that there is a positive relationship between efficiency and job satisfaction in many fields. This means that when performance increases, employees also feel satisfied with the work they do.